Effect of Exercise Countermovement Jump and Depth Jump against the Increase Agility and Leg Muscle Power - Irma Ferdiana; Muhammad Muhammad; Oce Wiriawan (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
The purpose of this study was to analyze the effect of Countermovement Jump exercises and Depth Jump exercises on agility and leg muscle power, as well as analyze which exercises are more influential between Countermovement Jump exercises and Depth Jump exercises on agility and leg muscle power. The research method used in this research is quantitative with pseudo experimental method, with research design using pretest and posttest, group I Countermovement Jump, group II Depth Jump, and control group, with data analysis using ANOVA. Data retrieval process is done by testing limb muscle agility using side step test tool and limb muscle power test with jump md tool, during pretest and posttest. Then the data is analyzed. The target of this study was taken from the population of female students of sports training education Surabaya state university with 30 members, divided into 3 groups with each group of 10 people, this study was conducted for 8 weeks. Paired sample t test results, Agility and paired sample t test strength of limb muscles are known that the significance level of each variable is obtained sig 0.000 <0.05 so that there is a significant influence or difference between pretest and posttest of variable bound agility and limb muscle power. Anova test results on agility and muscle strength of the limbs, showed Agility, sig 0.018, power sig 0.000, so it can be concluded that there are significant differences in the results of agility and limb muscle power in three different groups, known sig <0.05. From the results of the post-hoc multiple comparations (LSD) test independent variables that have a significant influence on increasing dependent variables, it can be seen from the average different results that the Countermovement Jump and Depth Jump groups have their own advantages with the results of the data obtained, meaning that countermovement jump and depth jump exercises are able to improve biomotor agility and power, but both have different influences.